Uporaba izbranih motivacijskih sredstev pri pouku glasbene vzgoje na razredni stopnji - Gorjanc, Tina; Kovačič, Bojan; Črčinovič Rozman, Janja (Revija za elementarno izobraževanje, 2013)
The Use of Selected Motivational Resources in Music Education at the Primary Level. The article presents some current findings on motivation and the way the latter correlates to the use of different motivational resources along with the results of an empirical study, the objective of which was to determine the importance of motivation for music teachers and the frequency of using selected motivational resources in music lessons at the primary school level. The latter has been explored by means of a questionnaire which was responded by 110 teachers from 12 primary schools in and around Maribor. The results of the study showed that there were statistically significant differences among the teachers based on their years of experience or the cycle of primary school, with regard to how often they used motivational resources such as pantomime, playing musical instruments, videos, and counting rhymes during their music lessons. However, there were no statistically significant differences among the respondents based on their years of experience or the cycle of primary school, with regard to significance they attributed to motivation. In fact, most of them stated that motivation was highly important. Based on the results obtained we came to a conclusion that though the teachers did realize the importance of motivation, this did not drive them to use some of the motivational resources more frequently.
Keywords: motivation; motivational resources; music lessons; class level